'CAR KIT' TO ENCOURAGE NOVICE TEACHERS TO CONDUCT CLASSROOM ACTION RESEARCH - Muchsonah Muchsonah (Jurnal Sosioteknologi, 2011)
Classroom Action Research has been introduced through seminars and workshops in Indonesia since 1990's. For experienced teachers, it has been a big help to provide another model of research which is considered effective as teachers' learning strategy. For novice teachers, however, action research is assumed to be an exclusive issue for it requires them to understand complicated terms and techniques. Moreover, various constraints such as teachers' limited time, scientific writing problems and insufficient knowledge resources often hinder teachers to carry out action research even in their own teaching practices. Therefore, there should be an effort to assist teachers to conduct an action research to cope with these constraints. Employing CAR KIT or Classroom Action Research Kit could be an effective starting point to conduct classroom action research. This instrument would be a very helpful means of inquiry during the process of research from planning, acting, observing and reflecting.